(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The purpose of this paper intended to study different heat treatments in conjunction with a special Cryogenic treatment process and its effect on the wear behavior, and hardness of AISI D2 tool steel. An experimental demonstration of this study was first carried out by a set of specimens left for one week in air after conventional treatment to make stabilization and the other set conditioned at 60°C for one hour before shallow and deep cryogenic treatment. This investigation has shown that an improvement of hardness and wear resistance in deep cryogenic (DCT) process compared to shallow cryogenic treatment (SCT) for different soaking time which was approved by micro-structural examination especially in the stabilized specimens. This finding is in agreement with other results found in the research using similar tool steel and other specific cryogenic processes.